Pathologies of the mind/body interface : exploring the curious domain of the psychosomatic disorders - Kradin, Richard L. (New York : Routledge, 2013)
"Unlike other texts on the subject, this book aims to provide a well-integrated approach to the diagnosis and treatment of the pervasive effects of the mind/body splitting that lead to somatoform disorders. Kradin explores the spectrum of currently recognized disorders with reference to the DSM-V formulations, as well as the medical, psychobiological, psychodynamic, and cognitive-behavioral approaches to these disorders. Additionally, he explores the role of developmental trauma in pathogenesis, and how stress, modulation, body-oriented therapies, Jungian-oriented embodied imaginal work, and psychopharmacological interventions can be integrated in the treatment of these disorders"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medicine, Psychosomatic; Mind and body; Electronic books